2013
DOI: 10.3906/biy-1209-24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new isolate of Malacosoma neustria nucleopolyhedrovirus (ManeNPV) from Turkey

Abstract: IntroductionBaculoviruses are enveloped viruses that have doublestranded, circular DNA genomes ranging in size from 80 to 180 kbp (1,2). Baculoviruses have been isolated from more than 600 insect species belonging to the orders of Lepidoptera, Hymenoptera, Diptera, Orthoptera, Coleoptera, Neuroptera, Thysanura, and Trichoptera (3). The most notable characteristic of baculoviruses is the occlusion body (OB). The occlusion body is a crystalline matrix composed of a protein called polyhedrin, which provides prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…PstI restriction analysis of both viral DNA shared the same bands and profiles. However, the KpnI and BamHI profiles of ManeNPV-T3 had more bands than the ManeNPV-T2 isolate with the same enzymes (Demir et al, 2013). Evaluation of these restriction profile differences showed that ManeNPV-T3 is different from the other ManeNPV isolates and is a new Turkish isolate of ManeNPV.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…PstI restriction analysis of both viral DNA shared the same bands and profiles. However, the KpnI and BamHI profiles of ManeNPV-T3 had more bands than the ManeNPV-T2 isolate with the same enzymes (Demir et al, 2013). Evaluation of these restriction profile differences showed that ManeNPV-T3 is different from the other ManeNPV isolates and is a new Turkish isolate of ManeNPV.…”
Section: Discussionmentioning
confidence: 95%
“…Scanning electron microscope results showed that ManeNPV-T3 has PIB sizes between 1.0 and 2.1 µm in diameter (Figure 2A). While these dimensions are greater than the PIB sizes of ManeNPV-T2 (Demir et al, 2013), the dimensions of OBs were within the usual size range of polyhedra. In a previous study, Ackermann and Smirnoff (1983) investigated the morphological characteristics of 23 baculoviruses that also include M. americanum, and reported that the mean dimensions of MaamNPV polyhedra varied between 1.1 and 1.7 µm, with an average of 1.44 µm.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Biopesticides and predators have a positive impact on bollworm population management (Ge and Ding 1996). Although effective systems are not yet operative against Helicoverpa sp., B. thuringiensis cry genes (Katı et al, 2007;Sevim et al, 2012) and nuclear polyhedrosis virus (Kozlav et al, 1994;Jankevica et al, 1997;Demir et al, 2013) have been utilized for M. neustria.…”
Section: Introductionmentioning
confidence: 99%